Analisis Kualitas Butir Soal Tes Literasi Sains Materi Listrik Dinamis untuk Mahasiswa PGSD - Siti Zahra Mulianti Natsir (GENIUS: Jurnal Inovasi Pendidikan dan Pembelajaran, 2026)
This study was motivated by the limited availability of scientifically validated science literacy assessment instruments, particularly on dynamic electricity material for pre-service elementary school teachers. Science literacy is an essential competency that prospective elementary school teachers must possess to understand scientific concepts and apply them in 21st-century learning. Instruments with low validity and reliability may lead to inaccurate measurement results; therefore, it is necessary to develop assessment instruments that meet good instrument criteria. This study aimed to analyze the quality of a science literacy test instrument in terms of validity, reliability, difficulty level, and discriminating power. The study employed a quantitative approach with a descriptive evaluative research design. The participants consisted of 40 students from the Elementary School Teacher Education Program. The research instrument comprised 25 multiple-choice items developed based on the PISA Science Framework 2025. Data were collected through instrument testing and analyzed using IBM SPSS Statistics. Expert validation results from two validators showed an average score of 4.42, categorized as very valid. The empirical validity test using Corrected Item-Total Correlation (CITC) indicated that 23 out of 25 items were valid, while two items were invalid. The reliability test yielded a Cronbach’s Alpha value of 0.971, indicating very high reliability. The difficulty level analysis showed that most items were in the moderate category, while the discriminating power analysis demonstrated that most items effectively distinguished between high- and low-ability students. This study contributes by providing a valid and reliable science literacy assessment instrument that can be used to evaluate science learning in elementary school teacher education programs.